PENGARUH KINERJA PENGAWAS SEKOLAH, KINERJA KEPEMIMPINAN KEPALA SEKOLAH, KINERJA PROFESIONAL GURU, DAN IKLIM SEKOLAH TERHADAP MUTU SEKOLAH DASAR BERDASARKAN KATEGORI SD RSBI, SSN DAN SPM DI DKI JAKARTA - Nuriah, Yuyun (2012)
Quality of education in Indonesia is still low, especially primary school. This is because of school management has not fully implemented a total quality management. Therefore, research on the influences of determinant factors of school quality is required. The objective of this research is to conduct in depth analysis the influences of the factors that have significant influence on the quality of primary schools in Jakarta with the proposed formulation of the problems, How the influence of variables Performance of School Supervisor (X1), Principal Leadership Performance (X2), Professional Performance of Teacher (X3), and School Climate (Y) to School Quality (Z). The method used in this research is survey method with quantitative approach, whereas the population is public elementary school in Jakarta. Because of the number of primary schools in each stratum is not proportional, the sampling is done with Disproportionate Stratified Random Sampling and obtained a 88 primary schools with the strata (categories) RSBI, SSN, and SPM. Data collection used in this study is through questionnaire and interview. Data were analyzed with the technique of path analysis by using statistical software program SPSS version 20. Result of this study shows that X1, X2, X3 variable simultaneously has significant influence to school climate (Y) on RSBI, SSN, and SPM. And the influence of X1, X2, X3, Y variable are simultaneously significant to School Quality (Z) on RSBI, SSN, and SPM. Individually, School Supervisor Performance variable did not significantly affect the School Climate on RSBI and did not significantly affect School Quality on SPM school category. Recommendation that can be delivered based on the result of this research is to improve the school quality by strengthening the school climate can be done by involving all school community to participate in the establishment of conducive school climate. In addition, there are needs to improve school supervisor's role in strengthening school climate, because based on the result of research the role of school supervisor to improve school quality and strengthening school clime has not been significant.